Customers' Complaints and its Determinants: The Case of a Training Educational Hospital in Iran - Hossein Ebrahimipour; Ali Vafaee-Najar; Ahmad Khanijahani; Arefeh Pourtaleb; Zoleykha Saadati; Yasamin Molavi; Shahnaz Kaffashi (Kerman University of Medical Sciences, 2013)
BackgroundToday, despite the efforts of the medical community and healthcare staff along with the advancements in medical technology, patients' dissatisfaction and complaints have been increased. The present study aimed at making a survey on the patients' complaints in a large training hospital affiliated to Mashhad University of Medical Sciences (MUMS). MethodsThis descriptive, cross-sectional study was conducted on written and verbal complaints of patients and their relatives in a tertiary (specialty and sub-specialty) training hospital. All the recorded patients' complaints, from March to December 2012, were reviewed. Data were categorized and analyzed using descriptive statistics by Microsoft Excel 2007. ResultsA total of 233 complaints were reviewed, of which 46.35%, 31.34% and 22.31%, respectively, were verbal, written and made on the phone. The main reasons for complaints were accessibility to medical staff (21.46%), communication failures (20.17%) and dissatisfaction with the provided care (14.59%). Thirty one (13.31%) cases were solved at first place, 194 (83.26%) referred to the complaints from the committee and 3.43% referred to the legal authorities. The average response time was about six to seven days. ConclusionThe findings of the study suggest that sufficient availability of medical staff, improvement in communication skills and paying attention to the patients' needs and expectations may reduce complaints from public health facilities.